Activated Carbon of Coconut Shell Modified TiO2 as a Batik Waste Treatment - Fery Eko Pujiono; Tri Ana Mulyati; Miftakhul Nor Fizakia (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2020)
Research about the modification of activated carbon of coconut shell with TiO2 as a waste treatment Batik has been done. The purpose of this study was to determine the effect of modified TiO2 on activated carbon characteristics and the effect of TiO2 concentration on the adsorption power of activated carbon in batik waste. The method utilized was activated carbon soaked in TiO2 with 5% and 10% concentrations in a ratio of 1: 5, then stirred with a magnetic stirrer for 2 hours. Next, the mixture was placed in an autoclave bottle and an oven (200°C for 30 minutes). The results were then washed with distilled water and dried (100°C for 5 hours), then the material was characterized by FTIR, XRD, SEM-EDX, and application to batik waste. FTIR results indicated the presence of Ti-O-Ti groups after modification at wave number 682 cm-1, XRD indicated the presence of a combination of amorphous KA and crystalline TiO2 at 25,2°; 37,7°; 48,1°; 53,8°; and 55°, and SEM results of TiO2 agglomeration on the surface of the railroad. Adsorption of batik waste showed KATiO2-10 (0,052) lower than KA (0,059) and KATiO2-5 (0,057), as well as the presence of COD KA results = 705,6 mg / L (pH = 8), KATiO2-5 = 504,0 mg / L (pH pH = 7) and KATiO2-10= 403,2 mg / L (pH = 7). Based on this research, the activated carbon modified TiO2 can be used as a material for processing batik waste with the most significant concentration of TiO2 represent 10%.